Do a science process skills affect on critical thinking in science? Differences in urban and rural - Darmaji Darmaji; Dwi Agus Kurniawan; Astalini Astalini; Rahmat Perdana; Kuswanto Kuswanto; Muhammad Ikhlas (International Journal of Evaluation and Research in Education (IJERE), 2020)
The study used mixed-method design. Sample size of this study was 689 students employed total sampling technique. This study revealed that science process skill of students in learning science whether urban and rural areas are good. The independent sample t-test showed that there was a significance difference in students' science process skill in urban school (M = 3.175, SD = 0.178) and in rural schools (M = 2.482, SD = 0.182); (t (687) = 18.224, p<0.01. The independent sample t-test showed that there was a significance difference in students' critical thinking in urban school (M = 5.058, SD = 0.163) and in rural schools (M = 3.436, SD = 0.152); t (687) = 17.224, p<0.001. Lastly, the regression shows the level of contribution students’ science process skill influence as much as 51.5% for critical thinking. This study was found that student science process skill affects critical thinking in learning science. Moreover, students' science process skill and critical thinking in urban better than rural.